Latar Belakang Legalisasi Tobacco Plain Packaging Bill 2011 di Australia - Ario Dwi Pranoto (Jurusan Ilmu Hubungan Internasional, 2015)
Australia has been a global leader in tobacco control and has implemented a comprehensive range of measures to reduce smoking rates and its harmful effects, including the introduction of plain packaging. Tobacco smoking is still one of the leading preventable causes of death and disease in Australia. Since 1 December 2012, all tobacco products manufactured in Australia is required to be sold in plain packaging under Tobacco Plain Packaging Bill 2011 which removes one of the last remaining forms of tobacco advertising. The legislation is consistent with the World Health Organization Framework Convention on Tobacco Control (WHO FCTC). Tobacco industry in Australia is strongly opposed to the Government’s proposal to require plain packaging of tobacco products.